SUFFERING AS SEEN IN GUY DE MAUPASSANT’S THE NECKLACE - Dewi Shinta Mamonto; Olga A. Rorintulus; Ceisy N. Wuntu (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This research was conducted to analyze Guy De Maupassant’s short story entitled The Necklace. This short story tells of a beautiful woman named Mathilde who experienced suffering not only mentally but also physically. The purposes of the study were to reveal suffering in the short story The Necklace written by Guy de Maupassant and the factors that cause suffering to the characters in The Necklace by Guy de Maupassant. The writer chose this research to examine this study from the short story The Necklace by Guy de Maupassant by using qualitative research. The writer uses two forms of data collection: primary source, the source of information from the work itself, The Necklace by Guy de Maupassant. Secondary sources are the sources that help the writer complete the research through articles, journals, dictionaries, and the internet related to this research and provide information to support the research study. The result of this study shows that Mathilde Loisel is a dreamer, never grateful, selfish, and hardworking. She always dreams of luxurious things in her life, and she only loves them. Therefore, she is never happy with her life. Unfortunately, she doesn’t realize that wealth is not everything in life. It happens when her best friend’s diamond necklace is lost. She does not tell her best friend about the real incident. Instead, she kept the secret for ten years. She thinks that her best friend’s diamond necklace is real, whereas it is fake.